Case study analysis : Tintas Robbialac SA acquisition of Tintas VIP - Martins, Diogo M. Vaz M. (2013)
The latest adjustment in the Portuguese Paints market has led the companies to reorganize their business plans as well as their core businesses and strategies. In the recent past, the market tends to follow a decreasing path over the Average Selling Price which forces Premium brands to expand their production to other market segments. Competing in a highly fragmented market, Tintas Robbialac SA decided to start operating in the medium-low segment by acquiring Tintas Vip. Being probably the best available solution to a quick and accurate penetration in the medium-low segment, Tintas Vip share deal reorganized the acquirer’s core strategy. The main issue in this acquisition was essentially the strategy. Competing in the medium-low segment became essential, but at the same time it was crucial for Tintas Robbialac SA to prevent the cannibalizing problem between parents and its subsidiaries activity. The successful management of these issues allowed the company to recover from the negative trend they were facing since 2000 on its market share. Although this acquisition did not observe the desired results in the first few years, it has been recovering and now it plays an essential role in Tintas Robbialac SA business. This thesis aims simultaneously to go through an acquisition in this market to analyse the effect that a purchase of a Medium-Low brand had in the strategy and the financial statements of a Premium company, and to study the accuracy of the acquisition in a brand’s valuation basis.